Studi Awal Keanekaragaman Serangga Menggunakan Light Trap di Habitat Sekitar Kawasan Gunung Jaboi, Sabang - Nisa Raudhatul Jannah; Novi Lestari; Ayuni Nabila; Refa Almaria; Selma Navisha Sofyana; Sheila Diva Cahyani; Maisal Jannah (Jurnal Bioleuser, 2025)
The Jaboi area in Sabang City is one of the areas with high biodiversity potential, but documentation of the types and populations of insects in this area is still very limited. This study aims to identify the types of insects found in the Jaboi area and evaluate the effectiveness of using light traps as a method for collecting insect samples. The method used was a field survey by installing light traps at several observation points for one night. The results showed that light traps were able to capture a large number of insects from various types of species, families, and orders, as the most dominant group. The diversity of light trap insects showed a moderate category to indicate that the Jaboi area has a complex and diverse insect community structure. Thus, the use of light traps has proven effective in detecting and inventorying insect diversity in tropical areas such as Jaboi, and can be an initial method in biodiversity studies and ecosystem monitoring in similar areas.